2015
DOI: 10.1016/j.jiph.2014.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Lebanese population for their knowledge, attitudes and practices of antibiotic usage

Abstract: Antibiotic-resistant bacteria has become a global phenomenon, mainly due to the inappropriate use of antibiotics. There are no studies in Lebanon to assess the public's knowledge, attitudes and practices (KAP) of antibiotic usage. A cross-sectional study was carried out using a self-administered questionnaire completed by a random convenience sample of 500 people. Nearly half of the respondents (46.1%) demonstrated moderate knowledge levels, while 40.6% demonstrated moderate attitudes. Although 80.2% knew that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

30
126
8
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(166 citation statements)
references
References 23 publications
30
126
8
2
Order By: Relevance
“…If the community could have correct knowledge, right attitude and good practice in antibiotic use, they could make it possible for reduction and even prevention of antibiotic resistance. Several factors that are associated with public knowledge regarding antibiotics use have been reported to be demographic characteristics, including gender (Barah and Gonçalves, 2010;Chang et al, 2012;You et al, 2008), age (Barah and Gonçalves, 2010), education level (Barah and Gonçalves, 2010;You et al, 2008), family income (Barah and Gonçalves, 2010;You et al, 2008) and place of residence (Mouhieddine et al, 2015). Moreover, social demographic characteristics and culture has been linked with practices towards antibiotics (Touboul-Lundgren et al, 2015), thus referred to as possible explanations of persistent differences in antibiotic consumption between countries.…”
Section: Introductionmentioning
confidence: 99%
“…If the community could have correct knowledge, right attitude and good practice in antibiotic use, they could make it possible for reduction and even prevention of antibiotic resistance. Several factors that are associated with public knowledge regarding antibiotics use have been reported to be demographic characteristics, including gender (Barah and Gonçalves, 2010;Chang et al, 2012;You et al, 2008), age (Barah and Gonçalves, 2010), education level (Barah and Gonçalves, 2010;You et al, 2008), family income (Barah and Gonçalves, 2010;You et al, 2008) and place of residence (Mouhieddine et al, 2015). Moreover, social demographic characteristics and culture has been linked with practices towards antibiotics (Touboul-Lundgren et al, 2015), thus referred to as possible explanations of persistent differences in antibiotic consumption between countries.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have reported that antibiotic regime non-adherence and in-appropriate antibiotic use are strongly associated with public awareness and knowledge of antibiotics [2][3][4][5]. Factors associated with public knowledge of antibiotics have been reported to be demographic characteristics, including gender [2,4,[6][7][8], age [6,[8][9][10][11][12], race [7,9], education level [3,4,[6][7][8][9][10][12][13][14][15], family income [4,8,14], place of residence [13,14], as well as other factors, such as lack of advice regarding rational antibiotic use, given by a physician [16]. Also, unregulated drug availability, inadequate antimicrobial drug quality assurance, inadequate surveillance and widespread attitude to antimicrobial misuse, include self-medication [17].…”
Section: Introductionmentioning
confidence: 99%
“…Findings from many studies have showed that inappropriate use of antibiotics is strongly associated with demographic characteristics, including education level (Hoffmann et al, 2014; Kim, Moon & Kim, 2011; Mouhieddine et al, 2015), family income (Barah & Gonçalves, 2010; Mouhieddine et al, 2015; You et al, 2008), place of residence (Godycki-Cwirko et al, 2014), as well as other factors, such as gender, age and parenting styles of the children (Bi, Tong & Parton, 2000). …”
Section: Introductionmentioning
confidence: 99%